IMPLEMENTASI QUANTUM TEACHING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENUMBUHKAN MINAT DAN HASIL BELAJAR DI SEKOLAH DASAR - Marisan Marisan; Aunurrahman Aunurrahman; Agung Hartoyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to describe the planning, implementation, evaluation and learning barriers of quantum teaching-based mathematics in growing interest and learning outcomes in state Elementary School 19 North Pontianak. Data is obtained by observation, in-depth interviews, field records and analysis of document data and teaching and learning process documentation. Research data is checked for its validity by triangulation in order to obtain accurate and legitimate data. Data analysis is done through data reduction, data display, verification and conclusion. The results of the research are: (1) The quantum teaching-based RPP mathematics made by the teacher is generally qualified in the manufacture of RPP; (2) The study of mathematics based on quantum teaching is implemented according to the program that has been drafted to foster the learning interest of learners, although sometimes it should adapt to the situation and condition of rill that occur suddenly; (3) The evaluation is not monotonous, evaluation of learning using several assessment instruments so as to make the teacher better understand how to foster learning interest and ability of learners (4) Learning mathematics based on quantum teaching requires supporting means of both multi-media learning, multi learning resources and so on. Keywords: Math learning, Quantum Teaching, growing learning interest, learning outcomes.